Access to Land and Tenancy Practices on Tanah Bengkok: Evidence from Java, Indonesia - Takashi Kurosaki; Saumik Paul; Firman Witoelar (Institute of Labor Economics (IZA), 2020)
Tanah bengkok (bengkok land) in Java, Indonesia boasts a unique institution where elected village leaders receive usufruct rights to a parcel of land owned by the village, in lieu of salary. Despite its relevance to the political economy of land distribution in Java, unavailability of systematic data has so far constrained in-depth empirical research on bengkok land. In 2018, we conducted a survey covering 130 villages and more than 1,800 households in Java. We found substantial heterogeneity in the incidence and use patterns of bengkok land across villages. Fixed rental tenancy appeared more prevalent than sharecropping on bengkok land and bengkok landlords seldom got involved in tenants' farming decisions, which made bengkok land management look more 'business-like'. Finally, evidence is consistent with political cycles as the village heads with reelection motives offered sharecropping contracts to non-relatives to garner a larger pool of supporters.
Keywords: H77; H83; O13; P14; O53; Q15; 330; Tanah bengkok; land tenancy; village administration; political cycle; Java; Indonesia